Third-Party Policing Approaches Against Organized Crime: An Evaluation of the Yakuza Exclusion Ordinances - Hoshino, Tetsuya (Journal of quantitative criminology, 2021)
Objective Third-party policing (TPP) refers to police efforts to persuade or coerce third parties to take some responsibility for crime control and prevention. The Yakuza Exclusion Ordinances (YEOs) of Japan aim to combat organized crime syndicates—the Yakuza. Consistent with the principles of TPP, the YEOs prohibit third parties (i.e., non-yakuza individuals) from providing any benefit to the yakuza. We argue that the effectiveness of the YEOs may depend on the strategic relationship among yakuza syndicates, where yakuza syndicates choose their power strategically to gain advantages over competition among rival yakuza syndicates. Methods We use unique data on the yakuza and construct a regional concentration index of yakuza syndicates. Exploiting prefecture-level variation in the YEOs’ enactment dates, we apply a difference-in-differences approach, while allowing for heterogeneity of the YEOs’ effect by the concentration of yakuza syndicates. Results The YEOs decrease the number of yakuza members and the effect of YEOs is greater in regions with lower concentration levels of yakuza syndicates. Given that yakuza members decrease by about 30% during the period of our study, our estimates suggest that the YEOs on average contribute to about 20% of a recent reduction of yakuza members. Conclusions The YEOs are related to TPP strategies that rely on coercive techniques, and thus our results suggest the effectiveness of TPP strategies against organized crime. Furthermore, the heterogeneity of the YEOs’ effect suggests the effectiveness of enforcement policies that intensively target regions with lower concentration of organized crime.